The Effectiveness of Osteopathic Treatment in Bowel Constipation Patients: A Clinical Perspective (Revista Contexto & Saúde, 2023)
Introduction: Functional chronic bowel constipation is a motility disorder of great relevance and prevalence worldwide. Objective: Analyze the efficiency of visceral manipulation technique in individuals with bowel constipation diagnose according to Roma III criteria. Methods: This is a crossover clinical study that included individuals of both genders aged between 20 and 40 years who had had bowel constipation symptoms for over one year. Individuals were randomized into two groups: the intervention (IG) and control (CG) groups. A four weeks washout period was given. Each volunteer underwent 24 individual osteopathic sessions, twice a week that lasted up to 30 minutes. Three intervention techniques were performed: two for the large intestine and one for the small intestine. Results: Thirty four patients were recruited but nine were excluded. Our sample consisted in 25 participants, 13 were allocated in the IG and 12 in the CG. No significant difference was found between groups for anthropometric, educational, marital status, proportion of smokers and alcoholics, and VAS for lumbar spine pain measures. Lumbar spine flexibility, was significant increased for the IG (p
Keywords: Osteopaty, constipation, Lifestyle